Infrastructure and Poverty: State Budget Effect Analysis with Panel Model - Nurul Azizah Az Zakiyyah (Journal of Asset Management and Public Economy, 2023)
The problem of poverty has an impact on various socio-economic problems such as high levels of illiteracy and unemployment, low levels of health and a bad environment. One strategy to reduce poverty can be done by building adequate infrastructure. The quality of advanced infrastructure is the main prerequisite needed by a country to accelerate its economic growth and development. This study focuses on the effect of infrastructure development that uses economic growth as a "bridge" in reducing the poverty rate that exists in Indonesia today. The contribution of this research is to find out how infrastructure budgeting affects poverty alleviation. The data used is panel data consisting of 32 provinces in Indonesia. The Fixed Effect model is the method used in this study, where the results show that the accelerated provision of priority infrastructure has a significant effect on poverty reduction. The availability of infrastructure services can encourage economic movement that reduces poverty. Partially, economic infrastructure, namely roads and clean water, has a significant effect on poverty alleviation, while social infrastructure DAU Education and DAU Health also have a significant negative effect . The results of this study have implications for the government where with the availability of adequate infrastructure it will be able to overcome poverty.